Exchange Rate Management a Chronicle Analysis in Afghanistan - arian, Ajmal (Journal of Social Sciences - Kabul University, 2023)
The main purpose of this effort is to provide a long-term chronicle analysis of the Afghani exchange rates, particularly against the US. dollar. The finding comes out from two sets of data (annual and daily) using the techniques of event analysis and some statistical tools. The historical analysis concludes two main stages and two sub-stage of development in the exchange rate market as a whole, pre institutionalization and post Institutionalization; collapse of the system and restructuring and construction of the system. On the other hand, the statistical finding points out that the exchange rate in recent years even of the gaining stability at initial suffered from depreciation and large volatility.